Adenomyosis at Hysterectomy: Prevalence, Patient Characteristics, Clinical Profile and Histopatholgical Findings - Shrestha, A; Shrestha, R; Sedhai, LB; Pandit, U (Kathmandu University Medical Journal, 2012)
Background Underlying adenomyosis is often the cause of treatment failure for patients undergoing medical therapy for abnormal uterine bleeding and or chronic pelvic pain. Given the limitation of ultrasonography in diagnosing adenomyosis and MRI being unaffordable to most of the patients belonging to developing countries like us, it often remains undiagnosed before a hysterectomy. Objective To find out the clinical profile associated with adenomyosis and to determine the prevalence of adenomyosis in hysterectomy specimens; frequency distribution, as well as to correlate clinical examination with histopathological examination. Methods A total of 60 women who had undergone hysterectomy with histopathologically proven adenomyosis between April 2009 and March 2010 were included . Data were collected on indication for the intervention, age, symptoms, clinical findings, hemoglobin, menopausal status, gross and histopathological findings. Results A total of 256 women were scheduled for hysterectomy. Adenomyosis was diagnosed in 60 of 256 cases (23.4%). Menorrhagia (91.2%), dysmenorrhoea (84.2%), lower abdominal pain (84.2%) beginning later in reproductive life (mean age- 45yrs) is the classic presentation. Adenomyosis was present in 10 of 61 patients (16.3%) with fibroids; 27 of 60 (45%) with abnormal uterine bleeding; 11 of 55 (20%) with prolapse; four of 35 (11.4%) with ovarian mass; five of 25 (20%) with chronic pelvic pain; three of four (75%) with endometriosis. Conclusion Women undergoing hysterectomy with diagnosis of adenomyosis have a distinct symptomatology. The choice of therapy in adenomyosis is hysterectomy for those women who have completed family and had failed medical therapy . KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 53-56 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6915